PENGARUH GAYA KEPEMIMPINAN DAN KREATIVITAS KERJA TERHADAP KINERJA PEGAWAI PADA BANK SULTRA CABANG UTAMA - Ayu Septiani; Abd. Azis Muthalib; Muhammad Nuzul Qadri (STIE ENAM ENAM KENDARI, 2022)
This study aims to determine and analyze Leadership Style and Work Creativity on Employee Performance at Bank Sultra Main Branch. either simultaneously or partially at the SULTRA Bank company. The population in this study was 314 respondents. A total of 75 employees of Bank SULTRA Main Branch. Based on the predetermined sampling criteria, the company met the requirements as a sample in this study. The data analysis technique used in this research is multiple linear regression model. Data processing was carried out using the SPSS 25 application program. The results of the study indicate that the leadership style and work creativity simultaneously have a significant influence on employee performance. The leadership style variable has a significant influence on employee performance. Work creativity variable has an influence on employee performance.